Mathematical Approaches to Quantum Computing Algorithms - Bijumon Ramalayathil; Aneesh Kumar K (Revista Electronica de Veterinaria, 2024)
Quantum computing has emerged as a revolutionary field that leverages quantum mechanics to perform computations exponentially faster than classical computers for certain problems. This paper explores the mathematical foundations and approaches underpinning quantum computing algorithms. The study delves into linear algebra, probability theory, group theory, and tensor calculus, which are integral to quantum algorithm design. Key algorithms such as Shor’s algorithm for integer factorization and Grover’s search algorithm are examined in detail, highlighting their mathematical structure and computational efficiency. The paper also discusses recent advances in quantum error correction and optimization algorithms for quantum systems.